Eucheumatopsis sanibelensis sp. nov. from the Gulf coast of Florida, USA - Peterson, Elias S.; Schneider, Craig W.; Saunders, Gary W. (Phytotaxa, 2020)
Based upon COI-5P, LSU rDNA and rbcL sequence data, as well as its morphological characteristics, a new red algal species, Eucheumatopsis sanibelensis E.S.Peterson, C.W.Schneider et G.W.Saunders sp. nov., was discovered on the Gulf coast of Florida, USA and shown to be distinct from the generitype E. isiformis with a type locality in the eastern Caribbean Sea. The new more attenuate taxon from Sanibel Island represents only the second species in this newly described genus, a genus recently segregated from Eucheuma based upon significant molecular and morphological differences. The two species have overlapping geographic distributions in the eastern Gulf of Mexico, but thus far E. sanibelensis is only known from a single location.